Raspberry Pi kukkubukku dai 4-han / = Raspberry Pi cookbook : - Monk, Simon (Orairī Japan, 2024)
"If you've started to work with Raspberry Pi, you know that Raspberry Pi's capabilities are continually expanding. The fourth edition of this popular cookbook provides more than 200 hands-on recipes (complete with code) that show you how to run this tiny low-cost computer with Linux, program it with Python, hook it up to sensors and motors, and use it with the Internet of things (IoT). This new edition includes new chapters on the Raspberry Pi Pico and machine learning with the Raspberry Pi."--
Keywords: Raspberry Pi (Computer); Python (Computer program language); Application software -- Development; Raspberry Pi (Ordinateur); Python (Langage de programmation); Logiciels d'application; Développement